Perception Of Workplace Mistreatment Among Subordinates Of Small-Medium Enterprises (Smes) In Punjab, Pakistan - Khaleel, Muhammad (2021)
The current study draws on the transactional theory of stress to propose that employees cope with workplace mistreatment by engaging in emotion-based coping in the forms of organization-directed deviance and psychological withdrawal. Specifically, this study aims that perceived hostile work environment, deep level dissimilarity with supervisor, and machiavellianism act as distal individual, organizational and environmental stressors. These stressors are transmitted through workplace mistreatment (abusive supervision and workplace ostracism) and that neuroticism moderates the proposed effects. This study was cross-sectional in design, and data was collected from the supervisors and the managers working in the SME sector in Pakistan. The results of the survey reveal interesting findings. In terms of direct hypothesis, all the findings were accepted except the relationship of machevillianism and workplace ostracism. Also, findings showed very contradictory results in terms of the moderating role of neuroticism. All the moderating hypotheses were accepted, showing role of neuroticism in enhancing the relationship between workplace mistreatment and coping strategies, except the role of neuroticism between workplace ostracism and psychological withdrawal. This study is one of its kind to have extensively examined the current situation of workplace mistreatment, its causes, and its consequences. To overcome workplace mistreatment, training policies and monitoring are needed urgently.